Periódicos de acesso aberto no Brasil: o cenário tecnológio no uso do SEER/OJS - Brito, Ronnie Fagundes de; Shintaku, Milton (Cadernos BAD, 2014)
Periódicos de acesso aberto no Brasil: o cenário tecnológio no uso do SEER/OJS